CARRYING CAPACITY OF BEEF CATTLE FODDER FORAGE FROM AGRICULTURAL WASTE IN THE TROPICAL ENVIRONMENT OF WEST JAVA PROVINCE USED GIS PROCEDURES - Perwitasari, Fitri Dian; Puspita, Iredo Bettie; Widiati, Rini; Putra, Ahmad Romadhoni Surya; Suwignyo, Bambang (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The application of Geographic Information System (GIS) in animal husbandry incorporates data on grazing variation and excretion behavior in ruminant species, information on various forms of land use, grasslands, and grazing management with agropastoral systems. This study aimed to 1) identify, inventory, and map land parameters from geographical conditions; 2) determine potential base areas for beef cattle development businesses in West Java Province; and 3) calculate the potential availability of forage feed from agricultural waste. This research was conducted from July 2020 to August 2021 in four districts in West Java Province, namely Cirebon, Majalengka, Indramayu, and Ciamis. Secondary data from 2016 until 2020, were taken by the Central Bureau of Statistics of each region. Data analysis includes 1) land cover mapping supported by (GIS), 2) air temperature and air humidity index (THI) suitable for beef cattle, and 3) agricultural waste carrying capacity (CC) and carrying capacity index (IK) for beef cattle. The results of land cover mapping show that shrubs, forests, and fallow land in the four districts can be used for fodder grass cultivation. In contrast, paddy fields, rainfed rice fields, and drylands produce agricultural waste as a source of fodder forage. THI values of 79.69 - 83.08 are suitable for beef cattle development. Based on the results of inventory and mapping conducted by CCI, it can be concluded that 30 sub-districts from four districts in West Java Province are potential areas for beef cattle development. CC agricultural waste can increase the availability of forage feed for cattle.